Experimental analysis of acupuncture's effects on hyperandrogenemia and related symptoms in PCOS patients - Yu-Xiao Liu; Yu-Xiao Liu; Yan-Hua Han; Yan-Hua Han; Yue Jiang; Yue Jiang; Jiao Zhang; Jiao Zhang; Yue-Hui Zhang; Yue-Hui Zhang (Frontiers in Medicine, 2025)
Traditional Chinese medicine (TCM) has seen a surge in interest in acupuncture as a treatment for polycystic ovary syndrome (PCOS), a condition marked by hyperandrogenism, irregular ovulation, and polycystic ovaries. Acupuncture has been shown to dramatically lower androgen levels in PCOS patients; this effect may be achieved by reducing the secretion of neurotransmitters in the hypothalamic-pituitary-gonadal (HPG) axis and interfering with the hypothalamic-pituitary-adrenal (HPA) axis and its cortisol release. Furthermore, by enhancing glucose metabolism, decreasing inflammation in adipose tissue, and enhancing intercellular communication pathways, acupuncture may indirectly address hyperandrogenemia. Although acupuncture has the potential to treat PCOS, further research is necessary to fully understand its mechanism. It is advised that more clinical research integrating molecular biology and biochemical methods be conducted in the future to determine the precise mechanism of acupuncture's effects on PCOS and to offer new suggestions for managing the condition's symptoms.